Liver Stiffness Measurements with MR Elastography: Agreement and Repeatability across Imaging Systems, Field Strengths, and Pulse Sequences - Trout, Andrew T.; Serai, Suraj; Mahley, Alana D.; Wang, Hui; Zhang, Yue; Zhang, Bin; Dillman, Jonathan R. (Radiology, 2016)
Purpose To prospectively assess agreement and repeatability of magnetic resonance (MR) elastography liver stiffness measurements across imager manufacturers, field strengths, and pulse sequences. Materials and Methods This prospective cross-sectional study was approved by the institutional review board; informed consent was obtained from all subjects. On the basis of an a priori power calculation, 24 volunteer adult subjects underwent MR elastography with four MR imaging systems (two vendors) and multiple pulse sequences (two-dimensional [2D] gradient-echo [GRE] imaging, 2D spin-echo [SE] echo-planar imaging, and three-dimensional [3D] SE echo-planar imaging). Each sequence was performed twice in each patient with each imaging system. Intraclass correlation coefficients (ICCs) were used to assess agreement and repeatability. P < .05 was considered indicative of a statistically significant difference. Results Pairwise ICCs were 0.67-0.82 and 0.62-0.83 for agreement between pulse sequences across manufacturers (n = 4) and field strengths (n = 5), respectively. ICCs were 0.45-0.90 for pairwise agreement between sequences while fixing manufacturer and field strength (n = 8). Test-retest repeatability across the various manufacturer, field strength, and pulse sequence combinations (n = 10) was excellent (ICCs, 0.77-0.94). The overall ICC for all manufacturer, field strength, and sequence combinations (n = 10) was 0.68 (95% confidence interval [CI]: 0.55, 0.82). ICC according to field strength was 0.78 (95% CI: 0.67, 0.88) at 1.5 T (n = 5) and 0.64 (95% CI: 0.49, 0.78) at 3.0 T (n = 5). ICCs according to vendor were 0.83 (95% CI: 0.73, 0.91) (n = 4) and 0.65 (95% CI: 0.51, 0.79) (n = 6). Average patient level variance was 0.042 kPa, with a coefficient of variation of 10.7%. Conclusion MR elastography is a reliable method for assessing liver stiffness, with small amounts of variability between imager manufacturers, field strengths, and pulse sequences. RSNA, 2016.